Osteosynthesis of mandibular angle fracture: Clinical case report (Research, Society and Development, 2024)
Maxillofacial trauma is intrinsically linked to a variety of physical injuries that compromise the anatomical structures of the upper, middle, and lower thirds of the face. In this context, the mandible stands out as one of the regions with the highest incidence of fractures in traumatic events. The objective of this study was to report a clinical case of mandibular fracture, detailing the step-by-step process from initial care to surgery to restore function and postoperative follow-up. This is an exploratory, descriptive, and qualitative case report. Data collection and use for the study were carried out following established ethical principles, in accordance with the international guidelines of the Declaration of Helsinki. The article describes the management of a mandibular fracture case resulting from a bicycle fall. After clinical diagnosis and completion of complementary and preoperative imaging tests, the patient underwent open reduction with internal fixation and was discharged the day after the procedure, without postoperative complications. The case reinforces the importance of a thorough clinical and radiological evaluation for an accurate diagnosis and for choosing the most appropriate therapeutic approach. Early intervention and correct alignment of bone fragments provide efficient healing, improving the patient's quality of life and reducing the risk of functional and aesthetic sequelae.